L'armée turque face à Chypre, la Grèce et l'Union européenne - Bozdemir, Michel (Études helléniques / Hellenic Studies, 2003)
The author of this article presents the counterview of the clichés often presented in regards to the Turkish Army, clichés which become a negative factor in the file for Turkey's candidacy to the E.U. If he regrets the Media over-exposure of the Military power, to which the public opinion listens more than to the civil one, the author estimates, however, that the Army is that of Turkey's institutions which is the most engaged on the road to Turkey's Westernization. If the Turkish military may be able to accept compromises, they would never abandon the two principles of their country: the secular and the unitary State.